Long-term survival after intrahepatic cholestasis of pregnancy: A follow-up of 571 mothers. (September 2019) - Hämäläinen, Suvi-Tuulia; Turunen, Kaisa; Mattila, Kari J.; Kosunen, Elise; Sumanen, Markku
Abstract: Objective: Intrahepatic cholestasis of pregnancy (ICP) is the most common liver disorder during pregnancy. ICP has been associated with morbidity but little is known about women's long-term survival. Our aim was to determine whether ICP is associated with mothers' long-term survival. Study design: The study population comprised 571 women with ICP in at least one pregnancy seen at Tampere University Hospital in Finland between 1969‒1988. The reference group comprised 1333 women: the previous and the following participant in the maternity ward diary. The data were obtained from Statistics Finland in March 2017 containing deaths among the study participants between 1971‒2015. The follow-up time of the cohort was 27–46 years. The Kaplan-Meier method was used. Results: Totally, 39 of the mothers with ICP (6.8%) and 111 of the reference group (8.3%) had died by the end of 2015 ( p = 0.267 ). The mean survival time of ICP women was 77.4 years and of the reference group 79.2 years ( p = 0.288 ). The mean survival time from labour in the ICP group was 45.0 years and in the reference group 44.8 years ( p = 0.259 ). Conclusions: Based on this study ICP does not seem to be associated with women's survival. There is no need to follow-up ICP mothers' health because of the nonexistent risk of premature death.